In-vitro efficacy of phytochemicals against Trichodinid ciliates infecting ornamental Goldfish, carassiusauratus - MANDIRA SAHA; SUBHASH MONDAL; P.K.BANDYOPADHYAY (International Journal of Pharma and Bio Sciences, 2017)
The ornamental fish trade plays an important role for socioeconomic upliftment of the backward people in our country with little investment of money. The business has been found to be a very profitable economic activity and deserves the scientific study and development. In spite of this lucrative business, India is suffering from loss due to the invasion of different ectoparasites. Trichodinids are known to be a major problem in fish farms causing serious damage, particularly under cultured condition. The wide varieties of antibiotics used for treating trichodiniasis not only make the environment unfavorable for aquaculture but the pathogen also becomes resistant towards the antibiotics over time. With the reminiscence in the use of herbal products, various botanicals have been heralded as crudes for particular pathogens, but the efficacy of these compounds for parasitic protozoa is questionable. Here, we tested a range of Basak (Adhatoda vasica) and Thankuni (Centella asiatica) plants extracts against a major aquarium pathogen, Trichodina sp. infecting the goldfish (Carassius auratus). Both the plant extracts significantly (P < 0.05 and P < 0.01) reduced parasite, and increased the survival time of fish in-vitro, after 5-10 days treatment only by using 4g and 8g food doses respectively. In a fully randomized experiment, the number of parasite was significantly reduced from infected fishes which were exposed to the mentioned phytochemical.The present study revealed that the use of these two phytochemical opened promising perspectives in terms of an alternative parasite treatment of chemical in aquaculture.